Total Hip Replacement : Case Series from a Leading Registry - Lampropoulou-Adamidou, Kalliopi; Hartofilakidis, George (Springer International Publishing : Imprint: Springer, 2017)
Setting out from the premise that "a picture is worth more than a thousand words", this book presents a superb set of illustrations, with accompanying clinical data, relating to a series of cases from a single surgeon registry. The series has the benefit of offering exceptionally homogeneous data from patients who have undergone total hip replacement (THR) and have been subjected to long-term follow-up with repeated acquisition of radiographs. This THR registry was established at the time when the Orthopaedic Department of the University of Athens became one of the first centers in Greece to perform THR. It now offers a huge database of unparalleled interest that includes approximately 1000 THRs performed by one of the authors (G. Hartofilakidis) between 1973 and 1994, with subsequent continuous follow-up. The cases with series of preoperative radiographs are of special interest, as they indicate the natural history of different types of hip disorders. In some cases of congenital hip disease, previous radiographs dating back to early childhood are available. Key messages and lessons learned are clearly spelled out. The book will be of high value for all orthopaedic surgeons who are interested in hip reconstruction surgery.